Dampak Pendapatan Asli Daerah dan Pendapatan Transfer dari Pemerintah Pusat terhadap Peningkatan Belanja Daerah di Provinsi Kalimantan Timur Tahun 2018-2022 - Tarisa Dana Shobiha; Diana Zuhroh; Tjandra Wasesa; Sutini Sutini; Wiratna Wiratna (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD) and Transfer Revenue from the Central Government on the increase in Regional Expenditure (Belanja Daerah) in East Kalimantan Province during the 2018–2022 period. The research utilizes a quantitative method with multiple linear regression analysis, employing secondary data sourced from regional budget implementation reports (APBD). The results indicate that PAD has a positive and significant effect on Regional Expenditure, meaning that an increase in the region’s own revenue contributes to higher spending capacity. Additionally, Transfer Revenue from the Central Government also demonstrates a positive and significant effect on Regional Expenditure. Both variables play an essential role in regional financial growth and public service provision. These findings suggest that optimizing PAD is crucial for improving fiscal independence and reducing dependency on central government transfers. Efficient management of Transfer Revenue is equally vital to ensure the sustainability of regional financial resources. This study offers valuable insights for local governments in East Kalimantan, particularly in their efforts to improve budget allocations, enhance fiscal autonomy, and foster sustainable economic growth. Furthermore, the study serves as a useful reference for developing sound regional financial policies to support the long-term development of East Kalimantan